The Marriage Agreement as an Effort to Prevent Domestic Violence (KDRT) - Sari, Ratih Mega Puspa (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Marriage is the first step for someone in forming a harmonious and happy family, because the realization of a sakinah, mawadah wa rahmah household is the true goal of marriage. This is what makes marriage a sacred agreement that must be maintained and its existence maintained. Although in marriage every couple has the goal of a peaceful, safe and peaceful family, in reality not all marriages can realize the goals of marriage itself. This can be caused by many factors, one of which is Domestic Violence (KDRT) committed by one of the parties, either the husband or the wife. A marriage agreement is generally known as a legal instrument that regulates the division of property between husband and wife. However, its role can be expanded to become a preventive tool in preventing domestic violence (KDRT). This study aims to examine the strategic role of a marriage agreement in forming a healthy and just household relationship. By using a normative approach and qualitative analysis of legal regulations and doctrines, it was found that a marriage agreement has the potential to provide a legal basis for protection for parties vulnerable to violence. However, its implementation still faces cultural and structural obstacles that need to be overcome through legal education and institutional strengthening.